Perencanaan dan Perancangan Bojonegoro Creative Hub Dengan Pendekatan Konsep Arsitektur Modern - Lukman Firdaus (Prosiding Sains dan Teknologi, 2022)
Bojonegoro Regency is one of the districts in East Java, which has a very fast industrial development, and Bojonegoro Regency itself has many natural resources including petroleum mines, teak forests, onyx stone mines, as well as abundant agricultural and plantation products. Meanwhile, the development of the creative economy in Bojonegoro is equally important. Many Micro, Small and Medium Enterprises (UMKM) actors and youth in Bojonegoro are pursuing the creative industry world with limited tools and facilities. Therefore, the planning and design of the Bojonegoro Creative Hub is very important, besides that, the Modern Architecture concept approach is the main attraction of the Bojonegoro people to move forward. The application of modern architectural concepts to the Bojonegoro Creative Hub is marked with several shapes and symbols that contain elements of modern architecture. One of the concepts inherent in the Bojonegoro Creative Hub is the Bengawan Solo River, because in ancient times the river was a means of supporting the economic activities of the Bojonegoro community, the Bengawan Solo River was also the center of cultural development in Bojonegoro. So that on this basis the Bengawan Solo river becomes the main concept of the building and is then packed through the development of modern times. With the existence of the Bojonegoro Creative Hub, the achievement of Bojonegoro to be more productive can be achieved. Keywords: Bojonegoro, Bengawan Solo, Modern Architecture, Creative Hub